A thermodynamically enhanced mechanical model to study the significant effect of air variation/transport on dynamic performances of magnetorheological dampers. (January 2019) - Guo, Pengfei; Xie, Jing; Guan, Xinchun
The instantaneously changing air content greatly affects the performances of magnetorheological dampers. However, the air variations/transport has been neglected in most previous studies. Based on open-system thermodynamics, a twin-bubble thermodynamic model is developed in this study, with the chambers taken as the open control volumes. It takes into account of the air variation/transport due to both the pressure change and the piston movement. Considering the dependence of the compressibility of air–fluid mixture on the air content, a thermodynamically enhanced mechanical model is then established, by combining the twin-bubble thermodynamic model with a mechanical model. To validate the proposed thermodynamically enhanced mechanical model, the damping forces of a magnetorheological damper (with a small amount of fluid leakage) were tested under different input currents and displacement excitations. The model predictions agree well with the experimental data. Due to the fluid leakage (i.e. large air content), the force–displacement hysteresis is not a desirable full rectangle, but a defective rectangle with two partially missing diagonal angles. The force–velocity hysteresis shows that force loss occurred when the piston changes its direction. Further, an experiment was performed on the high-temperature performance of the magnetorheological damper. The high temperature reduces both the yield force and the postyield viscous force. It also makes the force–displacement hysteresis fatter and the low damping force range smaller. A corresponding physical model is put forward, and its combination with the proposed thermodynamically enhanced mechanical model successfully captures the thermal effect. It is revealed that a prepressure is established and the air content decreases under high temperature.